Independensi Negara terhadap Bantuan Luar Negeri sebagai Bentuk Bela Negara - Sindy Yulia Putri (Peneliti.net, 2023)
The state has the highest authority to regulate various domestic and foreign policies, as well as policies for accepting and rejecting foreign aid (BLN). This paper aims to provide an overview of the independence of the state to accept and reject foreign aid to national interests at the time the assistance is offered. Referring to the foreign aid theory, donor countries have various motives when they distribute foreign aid to various recipient countries or partner countries, from humanitarian, diplomatic, trade or market expansion, and culture. Therefore, the author tries to explain that the state has the highest independence and supremacy. Independence is required by countries that accept and reject foreign aid as forms of state defense. Reflecting on Indonesia as a partner country, Indonesia has full rights and sovereignty to select various foreign aids that are in line with Indonesia’s political and economic interests. On the other hand, foreign aid which leads to limit Indonesian policies and reduce Indonesian sovereignty should be rejected with a diplomatic strategy. In fact, the Government of Indonesia and the governments of other partner countries need the awareness, participations, and full support of all components of society, so that they can live independently and not depend on foreign aid from any party.